Implant placement in the atrophic mandibular posterior region using the inferior alveolar nerve bypass technique after assessing the bone relative to the mandibular canal: A prospective interventional pilot study - Srivastava V.; Bansal R.; Chattopadhyay K.; Bansal M. (My University, 2025)
Introduction: Rehabilitation of the atrophic posterior mandible is very challenging because the distance between the crest of the ridge and the inferior alveolar canal (IAC) is very less. Inferior alveolar nerve bypass is a technique in which implants are placed bypassing the nerve, lingually or buccally. The objectives are to assess the bone around the mandibular canal on buccal and lingual sides and place implants in the posterior region of the atrophic mandible using the inferior alveolar nerve bypass technique. Materials and Methods:The bone with respect to IAC in 60 sites from 10 patients was assessed on both sides of the atrophic mandible.Measurements were taken at 10 mm, 20 mm, and 30 mm from the mesial aspect of the retromolar pad. After assessment, 20 implants were placed bypassing IAC in five patients, and postoperatively, neurosensitivity test was performed. Descriptive analysis was used to compare the different measurements from the retromolar pad on the right and left sides. Unpaired ‘t’ test was used. A P value less than 0.05 was considered as statistically significant. Results: The distance of the bone relative to IAC was statistically insignificant on right and left sides. Neurosensitivity test was negative on the first postoperative day. However, after the first and third months, there was positive response on the right side in 80% subjects and 100% on the left side. Conclusions: Dental implants were placed successfully in the atrophic mandible, bypassing the IAC. IAC is placed more lingually toward the medial border of the retromolar pad and then becomes buccally in the premolar region. Buccal bypass is safer and easier than lingual bypass due to the lingual position of IAC. © 2025 National Journal of Maxillofacial Surgery.